Global, Regional, and National Burden and Trends of Down Syndrome From 1990 to 2019 - Chen, Liyuan; Wang, Lifei; Wang, Yi; Hu, Haishan; Zhan, Yuan; Zeng, Zhilin; Liu, Lidan (Frontiers in Genetics, 2022)
Introduction: Down syndrome (DS) is the leading cause of genetically-defined intellectual disability and congenital birth defects worldwide. A large population of people diagnosed with DS globally are posing enormous socioeconomic burden. However, the global burden and trends of DS have not been reported. Methods: Based on the data from Global Burden of Disease database in 2019, we analyzed the incidence, prevalence, disability-adjusted life years (DALYs) and death of DS from 1990 to 2019 according to sex, age, regions and social-demographic index (SDI). Then, age-standardized rates (ASRs) and estimated annual percentage change (EAPC) of these indexes above were calculated to evaluate the temporal trend of DS. Finally, the association of SDI with DS epidemiological parameters was assessed. Results: In the past thirty years, the incident cases, age-standardized incident rate (ASIR) and age-standardized prevalent rate (ASPR) of DS first decreased slightly and subsequently increased globally. The number of prevalent cases increased steadily while the number and age-standardized rate (ASRs) of DALYs and deaths decreased gradually from 1990 to 2019. In the meantime, disease burdens were different across various SDI regions. The prevalent cases and ASPR for both sexes were increasing in all SDI regions except for the high-middle SDI region. At the national level, Brunei Darussalam, Ireland and Haiti were the top three countries with the highest ASIR in 2019. Georgia was in the top three with the highest increase in ASRs of four parameters, while Serbia was consistently ranked in the top three with fastest declining. Furthermore, we found that ASIR and ASPR were positively correlated with SDI, yet the age-standardized DALYs and age-standardized death rate (ASDR) were negatively correlated with SDI respectively. Conclusion: In the past thirty years, the burden and trends of DS were heterogeneous across different regions and countries with different sociodemographic characteristics. Great improvements had been achieved in reducing DALYs and deaths globally. However, the increased number and ASRs of incident and prevalent cases in some regions, especially in low SDI regions, were contributing to numerous challenges to public health. The findings may provide valuable information to the development or implementation of more effective measures.